2004
DOI: 10.1023/b:gene.0000039842.82574.02
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeny of Triatomine Vectors of Trypanosoma cruzi Suggested by Mitochondrial DNA Sequences

Abstract: The subfamily Triatominae (Hemiptera: Reduviidae) comprises hematophagous insects, most of which are actual or potential vectors of Trypanosoma cruzi, the protozoan agent of Chagas' disease (American trypanosomiasis). DNA sequence comparisons of mitochondrial DNA (mtDNA) genes were used to infer phylogenetic relationships among 32 species of the subfamily Triatominae, 26 belonging to the genus Triatoma and six species of different genera. We analyzed mtDNA fragments of the 12S and 16S ribosomal RNA genes (tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
32
0
13

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(54 citation statements)
references
References 28 publications
9
32
0
13
Order By: Relevance
“…In accordance with these species and subspecies concepts and in light of some previously published reports (Flores et al 2001, Martínez et al 2005, Takashi-Obara et al 2007, Bargues et al 2008, the biological evidence reported here supports the proposition that it is more appropriate to attribute a subspecies level to M. bassolsae, as has been proposed for M. pallidipen nis, M. longipennis and M. picturatus (Martínez-Ibarra et al 2008b). However, the same biological evidence supports the proposal that M. phyllosomus is a full spe cies, as some recent molecular studies have proposed (Sainz et al 2004, Pfeiler et al 2006.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…In accordance with these species and subspecies concepts and in light of some previously published reports (Flores et al 2001, Martínez et al 2005, Takashi-Obara et al 2007, Bargues et al 2008, the biological evidence reported here supports the proposition that it is more appropriate to attribute a subspecies level to M. bassolsae, as has been proposed for M. pallidipen nis, M. longipennis and M. picturatus (Martínez-Ibarra et al 2008b). However, the same biological evidence supports the proposal that M. phyllosomus is a full spe cies, as some recent molecular studies have proposed (Sainz et al 2004, Pfeiler et al 2006.…”
Section: Discussionsupporting
confidence: 77%
“…Biological and molecular studies on typical specimens (Mazzotti & Osorio 1942, Bargues et al 2008, Martínez-Ibarra et al 2008b) and on the naturally crossbred descendents of different individuals from sympatric populations (M. pallidipennis, M. longipennis and M. picturatus) (Martínez-Ibarra et al 2009) have lead to a proposal to reclassify some (M. pallidipennis, M. longipennis and M. picturatus) (Marcilla et al 2001, Martínez-Ibarra et al 2008b or all (Bargues et al 2008 of the six species of the genus Meccus to subspecies of M. phyllosomus. Other molecular and biological studies support the consideration of these groups as full species (Sainz et al 2004, Pfeiler et al 2006, Martínez-Ibarra et al 2008b). However, molecular evidence (Bargues et al 2008) supports the revalidation of the genus Meccus for the six species traditionally grouped into the Phyllosoma complex (Carcavallo et al 2000).…”
mentioning
confidence: 84%
“…These studies, showing biological evidence for the low degree of reproductive isolation among these four species of the genus Meccus, have been enhanced by recent molecular studies (Bargues et al 2000, Marcilla et al 2001) that support the proposition that six species of the Phyllosoma complex (including M. phyllosomus and M. bassolsae) should be considered as subspecies. On the other hand, other molecular studies (Sainz et al 2004, Pfeiler et al 2006) consider these species as valid ones. Since this debate has continued, knowledge about the degree of reproductive isolation of species of the Phyllosoma complex still needs to be improved.…”
mentioning
confidence: 99%
“…Several DNAbased techniques have been hitherto applied to triatomines Lyman 1999, Monteiro et al 2001). These include randomly amplified polymorphic DNA (RAPD) (Carlier et al 1996, Dujardin et al 1998a, Noireau et al 2000a, Borges et al 2000, Jaramillo et al 2001, Pacheco et al 2003, species-specific length variation of rDNA amplicons (Jaramillo et al 2001), single strand conformational polymorphism analysis , sequencing of selected nuclear (Monteiro et al 2000, 2001 and mitochondrial gene fragments (García and Powell 1998, García et al 2001, Gaunt and Miles 2002, Hypša et al 2002, Sainz et al 2004, and characterization of polymorphic microsatellite markers (Harry et al 1998, Anderson et al 2002). …”
mentioning
confidence: 99%